Frequent Antenatal Care Visits Increase Institutional Delivery at Dabat Health and Demographic Surveillance System Site, Northwest Ethiopia - Abel Fekadu; Mezgebu Yitayal; Geta Asrade Alemayehu; Solomon Mekonnen Abebe; Tadesse Awoke Ayele; Amare Tariku; Gashaw Andargie; Destaw Fetene Teshome; Kassahun Alemu Gelaye (Hindawi Limited, 2019)
Background. Early diagnosis of pregnancy, professional follow-up, and skilled delivery service are the main interventions that reduce maternal morbidity and mortality. Generating local based evidence could support targeted and effective intervention placed by a government. Therefore, determining the prevalence of skilled institutional delivery and its associated factors is of supreme importance. Methods. A community based cross-sectional study was conducted among pregnant women at Dabat Health and Demographic Surveillance System (DHDSS) site from 2014 to 2015. A total of 1290 pregnant women were included in the study. Data were extracted from what was collected as part of the ongoing DHDSS. Variables were extracted from the Household Registration System (HRS2 version 2.1) database and exported to STATA version 14.1 for analysis. Binary logistic regression was used to identify the factors associated with skilled institutional delivery. Statistical test was considered significant at P value < 0.05. Results. The proportion of skilled institutional delivery was 31.0% (95% CI: 28.5, 33.6). Frequent Antenatal care (ANC) visits (Adjusted Odds Ratio (AOR): 2.94; 95% CI: 1.75, 4.94)), living in urban setting (AOR: 9.54; 95% CI: 5.99, 15.17), and ability to read and write (AOR: 1.81; 95% CI: 1.18, 2.75) were factors associated with increased delivery in the health institutions. On the other hand, giving more number of births (AOR: 0.39; 95% CI: 0.22, 0.66) decreased health institution delivery by 61%. Conclusion. Higher rate of skilled institutional delivery has been observed at the surveillance site as compared with the previous national estimates. Giving less number of births, frequent ANC visits, being in urban residence, and ability to read and write increased the likelihood of health institution delivery. Strengthening interventions that could influence the identified factors could improve mothers' choice to skilled institutional delivery.